Composition and Distribution of Invasive Species in The Peson Subah I Nature Reserve, Batang District, Central Java - santoso, budi; Kurniayu, Tiara Putri (Al-Hayat: Journal of Biology and Applied Biology, 2024)
Research has been carried out regarding the composition of invasive plants in the Peson Subah I Nature Reserve (PSINR), a conservation area located at Kuripan Village, Subah District, Batang Regency Central Java. The research, which was carried out from 17 to 20 April 2023, aims to identify invasive plants in PSINR and mapping their spatial distribution. This research used a double plot method which was determined purposively with a sampling intensity of 10%. The analysis method used is quantitative descriptive based on the parameters of the vegetation analysis results. Based on the results of observations, 80 plant species were found, of which 53% or 43 species were invasive species. The highest Importance value Index for the invasive species at each tree level is Acacia (Acacia auriculiformis) 66.44, at the pole level it is Klampis (Flacourtia indica) with an Importance value index of 91.46, at the sapling level it is Lampeni (Ardisia elliptica) and at the seedling level the invasive species Lampeni (Ardisia elliptica) 55.16. The plant diversity index in PSINR at each growth level is in the medium category, while the evenness index is in the high to medium category.